IMPLEMENTASI AKAD IJARAH MULTIJASA SEKTOR PENDIDIKAN: STUDI KASUS BANK CIMB NIAGA SYARIAH - Muhammad, Rifqi; Lailatul Fatmawati, Nur (Ekonomi Islam, 2020)
One of the Islamic banking products that is quite flexible is multi-service Ijarah. This paper aims to analyze the implementation of multi-service ijarah contracts in one of the Islamic banks, especially for financing the education sector. The implementation of multiservice ijarah financing is carried out in accordance with the Fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) by combining the ijarah contract and the wakalah contract. However, there are still obstacles to identify financing objects in this education sector. In addition, the status of using the wakalah contract as a supporting contract is still unclear in the practice of multi-service ijarah. The issue of the imposition of fines by banks is also an important discussion as a solution to provide optimal services for customers who need financing in the education sector. Keywords: multi-service ijarah, fines, and education sector